2022
DOI: 10.1186/s12891-022-05561-w
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of Intervertebral Disc detectable by T2-weighted MRI and its correlation with curve severity in Adolescent Idiopathic Scoliosis

Abstract: Background Our previous studies found disproportionate anteroposterior vertebral size is associated with severity of the scoliotic curves in adolescent idiopathic scoliosis (AIS) patients. Subsequent studies showed wedging of vertebral bodies (VB) had less contribution than intervertebral discs (IVD) to the anterior–posterior vertebral column length discrepancy in severe-AIS. However, the exact morphological changes of IVD were not clearly defined. This study aimed to evaluate the morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…As life expectancy increases worldwide, degenerative diseases of the lumbosacral spine are becoming more common[ 1 ]. Debilitating conditions are currently the major causes of morbidity, disability, and lost productivity[ 2 , 3 ]. The current treatment of choice for spine degeneration is laminectomy for nerve root decompression.…”
Section: Introductionmentioning
confidence: 99%
“…As life expectancy increases worldwide, degenerative diseases of the lumbosacral spine are becoming more common[ 1 ]. Debilitating conditions are currently the major causes of morbidity, disability, and lost productivity[ 2 , 3 ]. The current treatment of choice for spine degeneration is laminectomy for nerve root decompression.…”
Section: Introductionmentioning
confidence: 99%
“…So, we planned a study in which to test promising candidate epigenetic AIS markers in bone, muscle, and ligament tissues positioned at the scoliotic curve. The literature data also suggested that disease onset and progression may involve other tissues, such as the intervertebral disk and vertebral body [47]. Nevertheless, we have not included these tissues in our proposed workflow, since the surgical procedure for treating AIS employs an "all posterior" approach, which does not allow direct manipulations on the intervertebral disk or vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal chondrogenic differentiation can lead to abnormal morphological changes in the intervertebral disc, articular cartilage, and endochondral ossification. T2‐weighted magnetic resonance imaging in patients with AIS has revealed that the position and morphological changes of the intervertebral disc are correlated with the severity of the curve (Yeung et al, 2022). Additionally, there is a significant increase in the number of balloon cells on the concave side of the spine, but almost no increase in the number of these cells on the convex side (Sitte et al, 2013).…”
Section: Research On Bmsc‐mediated Ais Pathogenesismentioning
confidence: 99%
“…Abnormal chondrogenic differentiation can lead to abnormal morphological changes in the intervertebral disc, articular cartilage, and endochondral ossification. T2-weighted magnetic resonance imaging in patients with AIS has revealed that the position and morphological changes of the intervertebral disc are correlated with the severity of the curve (Yeung et al, 2022).…”
Section: Chondrogenic Differentiation and Aismentioning
confidence: 99%